Exile, ostracism, and democracy : the politics of expulsion in ancient Greece - Forsdyke, Sara, 1967- (Princeton University Press, 2005)
This book explores the cultural and political significance of ostracism in democratic Athens. In contrast to previous interpretations, Sara Forsdyke argues that ostracism was primarily a symbolic institution whose meaning for the Athenians was determined both by past experiences of exile and by its role as a context for the ongoing negotiation of democratic values. The first part of the book demonstrates the strong connection between exile and political power in archaic Greece. In Athens and elsewhere, elites seized power by expelling their rivals.